Outros professores que passaram pelo PPGG/UFRJ - Espaço Aberto, Revista (Espaço Aberto, 2022)
Prof. Milton Santos (1926-2001) Profa Maria Luiza Fernandes Pereira Profa Leila Christina Duarte Dias Prof. Carlos Minc Baumfeld Profa. Irene Ester Gonzalez Garay Prof. Elmo da Silva Amador (1943/2010) Profa. Ana Clara Torres Ribeiro (1944-2011) Prof. João José Bigarella (1923-2016) Prof. Hélio Monteiro Penha (1949-2009) Prof. Rafael Straforini Prof. Antônio Paulo de Faria Prof. Eduardo José Pereira Maia